Wide-range refractive index sensing relied on tracking the envelope spectrum of a dispersive subwavelength grating microring resonator. (October 2022) - Xu, Yameng; Fu, Chenyang; Sun, Shibo; Kong, Mei
Highlights: The wide-range and high-sensitivity refractive index sensing is proposed. The device is based on a subwavelength grating microring resonator. The dispersion effect of the device is applied to generate an envelope spectrum. The refractive index sensing is relied on tracking drift of the envelope spectrum. This work offers a scheme for broadening the detectable range of sensors. The device is a promising candidate for lab-on-a-chip in future work. Abstract: The detectable range is a critical parameter to characterize refractive index sensing performances besides the sensitivity. We theoretically demonstrate a wide-range refractive index sensing based on a dispersive subwavelength grating microring resonator by tracking the drift of its envelope spectrum with the refractive index. We exploit the dispersion engineering of subwavelength grating waveguides to tailor the wavelength dependence of the critical coupling condition and consequently the dispersion of the subwavelength grating microring resonator to form an envelope spectrum centered at critically coupled wavelength. Through monitoring the envelope spectrum, the detectable range of the refractive index sensing can be effectively broadened rather than limited by the free spectral range of the microring resonator. Meanwhile, the high sensitivity of the subwavelength grating microring resonator can be inherited. A detectable range up to 0.5 RIU and a sensitivity of 600 nm/RIU are achieved based on the dispersive subwavelength grating microring resonator. This study offers an effective scheme for broadening the detectable range of microring resonator sensors and a new candidate for high performance integrated sensors.